Improving Gross Motor Skills Learning Through Traditional Games For Fifth-Grade Students at SDN Cileutik - Pramesty, Ajeng Widya; Lengkana, Anggi Setia; Rukmana, Anin (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research aims to improve the gross motor skills of students at SDN Cileutik, which are not yet optimal. This research aims to improve gross motor skills through traditional games such as engklek for fifth-grade students at SDN Cileutik. This research was conducted at SDN Cileutik in Physical Education for fifth-grade students in the 2024/2025 academic year, involving 26 students—13 boys and 13 girls. Classroom Action Research is the method used. The research design uses the Kemmis and McTaggart model, which focuses on cycles of reflection and continuous action. This research was conducted in three cycles, each consisting of planning, action implementation, monitoring and evaluation, and analysis and reflection. Observation sheets of student and teacher activities were used to collect data during the monitoring and evaluation phase. The data was then analyzed using quantitative and qualitative methods. In the first cycle, only three people completed it, resulting in a graduation rate of 11.54%. In the second cycle, 21 people graduated, achieving a graduation rate of 80.77%. In the third cycle, all 26 participants completed it, achieving a graduation rate of 100%. This shows that the teacher-student activities in the first, second, and third cycles successfully met the requirements of the learning process. Based on the data above, the use of traditional games can improve gross motor skills.